Clinical Doctorate:A Professional Degree in Occupational Therapy Education - Keli MU; Angela PATTERSON; Anna DOMINA; Yali WANG; Yumeng WANG (康复学报)
With the rapid development of rehabilitation in China, professional education in occupational therapy(OT)has witnessed significant expansion and changes in recent years. Professional doctorates in OT and other health care professions have gained increasing attention and popularity in China. Confusion exists for emerging professional doctorates in China and the international community. The purpose of this article is to introduce and describe the concept of professional doctorates, with an emphasis on doctor of occupational therapy(OTD)degree. Training and education of a professional doctorate in OT is illustrated via an OTD program in the USA. And the increased residency/fellow program after post OTD graduation was explaind and discussed. This review will provide guidance for the development of OT education in China.